PENGGT]NAAN MEDIA TRANSPARANSI OHP SEBAGAI ALAT BANTU INSTRUKSIONAL PENGAJARAN IPA DENGAN PENDEKATAN KETRAMPILAN PROSES SEBAGAI UPAYA UNTUK PENINGKATKAN KUALITAS PENDIDIKAN IPA - FAUZI, AHMAD (BIOEDUKASI, 2006)
AbstractThe aims of this research are to find out: (1) the intluence of using the OHP mediq and LKS (l,embarKerja Siswa,/student worlcsheet) to raise the quality of scientific education (2) the influence using demonstrationmethod and information discussion method to raise the quality of scientffic subject education (3) interaction offactor 1 andfactor 2 in raising the quality of scientific education.The research used the experiment method with 2X2 factorial design. The researcher collected the databy giving test to the subject. The population of the research was the third grade of senior high school (MTsN)Salatiga, the number of the samples were 80 students (divided into two classes), taken from sub-populations of268 students (in six classes). The researcher applied random sampling technique. The data was analyzed byusing ANOVA at the level of significance d = 0,05.The results showed that: (1) there is a significant dffirence of using the OHP and LKS in rising thequality of scientific subject education (2) there is significant dffirence of using the demonstration method andinformation discussion method in rising the quality of scientific subject education (3) there is no interactionbetween the usage of OHP transparence and LKS with the usage of demonstration and information discussionmethod to raise the quality of scientffic education.Keywords: transparence, OHP, dffirence influences, scientific subject education.